Analysis of Workload, Competence, and Workplace Discipline Effects on Employee Performance - Kurniawan, Roni (Sekolah Menengah Kejuruan (SMK) Pustek, 2023)
Employee work discipline is able to improve performance related to the sense of responsibility of employees in carrying out their duties effectively and efficiently. The purpose of this study was to determine the effect partially or simultaneously between Competence, Work Discipline and Workload on Employee Performance at the Regional Financial and Asset Management Agency for the City of South Tangerang. This research method is an associative research type. The population and sample in this study amounted to 110 respondents, using a saturated sampling technique. Technique Analysis data using Analysis simple and multiple linear regression. The results showed that there is a Simultaneous Positive and Significant Influence between Competences (X1), Work Discipline (X2) and Workload (X3) Against Performance (Y).